Relexification in a Northern Norwegian dialect? - Sollid, Hilde (Nordlyd, 2004)
This paper explores how the process of relexification can contribute to the understanding of the genesis of the new Norwegian dialect of Sappen in Nordreisa. The dialect has emerged in the context of language shift from Finnish to Norwegian, and the dialect syntax has features that might be regarded as products of relexification. One example is declarative main clauses with the finite verb in the third position (V3). The discussion adheres to a more general discussion of approaches to language genesis, where substratist and universalist (and also superstratist) theories often are regarded as contrary to each other. I argue that different theories can contribute to the understanding of different aspects of the same question.